Microbial community responses to freeze : thaw cycles in active layer soils of permafrost tundra, Disko Island, Greenland - Gough, Isabelle (SLU/Dept. of Soil and Environment, 2019)
Permafrost affected soils are a vast pool of Carbon, storing around 1300Pg below the ground. As a result of climate change, permafrost soils that have been frozen for thousands of years are thawing, causing the ancient organic matter to be metabolised by microorgan-isms. Moisture content of soils has an impact on microbial community activity, but the mechanism of this effect is poorly understood. This study sought to explore the effect of microbial alpha and beta diversity, microbial activity, and greenhouse gas production respond to thaw in wet and dry soils in the Arctic. Soils were selected from a wet fen and dry sedge heath from Disko Island, Greenland to test the effect of soil type on thaw. Microbial community dynamics were studied over the thaw period using amplicon sequencing of 16S (bacteria) and ITS (fungi). It was found that although alpha and beta diversity did not sig-nificantly respond to thaw, enzyme activity did have an effect, sug-gesting that microbial community behaviour had been affected. The impact of this on greenhouse gas fluxes were that the dry soil became a sink of CO2, N2O and CH4, whereas the wet soils became a source of all three gases. This finding indicates that moisture regime will play a large role in whether artic soils will contribute to climate feedbacks upon thawing.